THE ROLE OF INCLUSIVE EDUCATION IN DEVELOPING A CULTURE OF HUMANITY IN PRESCHOOL CHILDREN (Academicia Globe: Inderscience Research, 2022)
The article is devoted to the formation of a humane culture in preschool children in the context of inclusive education, which plays an important role in improving the quality of education in preschool education.